The relationship between humic acid (HA) adsorption on and stabilizing multiwalled carbon nanotubes (MWNTs) in water: Effects of HA, MWNT and solution properties - Lin, Daohui; Li, Tingting; Yang, Kun; Wu, Fengchang (Journal of hazardous materials, 2012)
► MWNT-surface area-normalized HA adsorption increased with increasing MWNT diameter. ► HA with higher polarity was adsorbed less by but stabilized more amount of MWNTs. ► MWNT stabilization increased and then leveled off with increasing HA adsorption. ► Ionic strength and pH affect relationship between HA adsorption and MWNT suspension. This study was aimed to explore the relationship between humic acid (HA, as a model NOM) adsorption on and stabilizing multiwalled carbon nanotubes (MWNTs) in water with a focus on the effects of HA, MWNT and solution properties. It was found that MWNT-surface area-normalized adsorption of HAs (QSA) increased with increasing outer-diameter of the MWNTs and decreasing polarity of the HAs. However, at low pH values (ca. <4) or high ionic strengths (ca. >1mmolL−1 Ca2+), the HA adsorption decreased with decreasing polarity of the HAs. The MWNT stabilization increased with increasing QSA, but the increase leveled off when QSA exceeded a threshold value markedly lower than the maximum QSA, especially for the MWNTs with relative large outer-diameters. On the whole, the QSA-normalized MWNT stabilization, presenting the capability of the MWNT-adsorbed HAs for the MWNT stabilization, increased with increasing HA polarity and solution pH, but with decreasing Ca2+ concentration. However, the stabilized MWNTs by the HAs with greater polarity could be more subject to destabilization by Ca2+. The results of this study are believed to shed light on predictive understanding the interaction between MWNTs and NOM and the environmental behavior of MWNTs.